FORMULATION AND PENETRATION TESTING OF ETHOSOME AZELAIC ACID ON ABDOMINAL SKIN WHITE MALE RATS (RATTUS NORVEGICUS) WITH FRANZ DIFFUSION CELL - Nurleni, Novi; Iskandarsyah, Iskandarsyah; Aulia, Ahmad (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Development of transdermal drug delivery systems has several advantages, especially drugs to have a poor penetration of stratum corneum in the skin. Azelaic acid has been proven bactericidal and bacteriostatic to acnes bacteria (Propionibacterium acnes). Azelaic acid products in market as cream and gel can only penetration in stratum corneum about 4% of the dosage used. Thus, it is necessary to increase the penetration of azelaic acid to formulate into a carrier system such as ethosome. Methods: Manufacture of suspension ethosom azelaic acid using thin layer hydration method or classical method. Suspension ethosom of azelaic acid to obtained subsequent freeze dried before formulated in cream preparation. After that, the penetration test for ethosom cream and non ethosom cream of azelaic acid with Franz Diffusion Cell. Results: Optimization formulation ethosom of azelaic acid with variations concentration of ethanol 30%, 35% and 40%. Ethosome with 35% ethanol had entrapment efficiency higher than 30% and 40% ethanol as 94.48±0.14% and had smaller particle size 179.3±2.23 nm. Penetration test for ethosome cream and non-ethosome cream of azelaic acid showed that cumulative amount was 1334.074±27.086 μg/cm2 h and 491.032±3.935 μg/cm2 h. Conclusion: Ethosome cream of azelaic acid has better penetration capabilities than non-ethosom cream of azelaic acid.